2018
DOI: 10.36001/phmconf.2018.v10i1.549
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Prognostics of Fatigue Crack Growth in Notch Pre-cracked Aluminum 7075-T6 Rivet Hole

Abstract: Constant stress amplitude fatigue tests were conducted on the notch pre-cracked Aluminum 7075-T6 rivet hole dog-bone coupons. Monitoring of visible surface crack length by special surface engraving using digital microscope images and by ultrasonic sensors signals was carried out to yield fatigue crack length measurements in relation to number of fatigue cycles applied. The experimental results provide ultrasonic sensor validation for fatigue crack length measurements. Fracto-graphic examination of failed fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The physical meaning is that the slope of the N – a curve is larger than the real value, which means an unstable crack growth. Similar work can be found in Haynes et al 153 Ma et al 154 developed an FNN model for a – N curve extrapolation with small data size in another recent work. The data on the first part of the curve is used as training data to predict the remaining part, as shown in Figure 12.…”
Section: Review Of Nn Applications In Fatiguesupporting
confidence: 61%
“…The physical meaning is that the slope of the N – a curve is larger than the real value, which means an unstable crack growth. Similar work can be found in Haynes et al 153 Ma et al 154 developed an FNN model for a – N curve extrapolation with small data size in another recent work. The data on the first part of the curve is used as training data to predict the remaining part, as shown in Figure 12.…”
Section: Review Of Nn Applications In Fatiguesupporting
confidence: 61%
“…Several authors have applied ML-based models for the prediction of fatigue crack growth. [30][31][32] Shiraiwa et al 33 have combined FEA and ML-based methods (artificial neural network, henceforth ANN) to predict the fatigue performance of welded structures. Kadi and Al-Assaf 34 employed an ANN to predict the fatigue of unidirectional composites.…”
Section: Introductionmentioning
confidence: 99%
“…Haynes e al. [7] reported that the NASGRO and AFGRO approaches to predict the fatigue life cycles were found to be incorrect by ten-folds because of its inability to predict equivalent initial flaw size. An et al [8] used Bayesian approach using Markov Chain Monte Carlo (MCMC) technique to predict fatigue life of the turbine components using available field data.…”
Section: Introductionmentioning
confidence: 99%